2000
DOI: 10.1002/1097-4628(20001209)78:11<1923::aid-app110>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Degradation cracking of poly(ethylene terephthalate) filaments by methylamine andN-propylamine

Abstract: Poly(ethylene terephthalate) (PET) filaments were degraded with aqueous solutions of n‐propylamine and methylamine. The treated materials were examined by chemical microscopy and physical and mechanical methods. After partial degradation by aqueous solutions of amines, the surfaces of the filaments cracked. Direct observations of the cracking pattern formation and the changes in the physical properties of the filaments led to an explanation for the cracking pattern formation. The cracked patterns showed the sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Such a phenomenon could bring about a plateau value after a peak in the number of amines present on PCL due to the detachment of the interested portion of the PCL chain at a longer time of treatment. Crack formation as well as a massive loss of mechanical properties after partial degradation during aminolysis is already reported, mainly in the case of PET. , The influence on bulk properties and the control over the surface chemistry and evolution during the treatment of its physicochemical properties were studied as key aspects. In particular, it was demonstrated that the bulk mechanical properties are not significantly affected by aminolysis in the proposed reaction conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Such a phenomenon could bring about a plateau value after a peak in the number of amines present on PCL due to the detachment of the interested portion of the PCL chain at a longer time of treatment. Crack formation as well as a massive loss of mechanical properties after partial degradation during aminolysis is already reported, mainly in the case of PET. , The influence on bulk properties and the control over the surface chemistry and evolution during the treatment of its physicochemical properties were studied as key aspects. In particular, it was demonstrated that the bulk mechanical properties are not significantly affected by aminolysis in the proposed reaction conditions.…”
Section: Discussionmentioning
confidence: 99%
“…From this functional group transformation, PET was modified or degraded by reaction with various amines. For instance, PET fiber surface was modified by using 3-aminopropyltriethoxysilane [2,3], n-butylamine vapor and aqueous nbutylamine [4], n-propylamine and methylamine [5], by diamines [6] or by multifunctional amines [7]. The aminolytic depolymerization of PET with ethanolamine has been investigated under reflux in the presence of glacial acetic acid, Trang 102 sodium acetate and potassium sulphate, as catalysts [8], or under microwave energy and using catalysts [9], or under microwave irradiation and without the use of any catalyst [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors reported the aminolysis reaction of esters by amines. All these reports can be divided into two fields, that is, study of PET morphology18, 19 or application of the aminolysis to practical uses 20. This reaction is based on the nucleophilic reaction of an amine with the ester bonds along a polymer chain and results in polymer‐chain scission.…”
Section: Introductionmentioning
confidence: 99%